Teacher’s Mindset and Mathematical Competencies Development: An Appraisal of Intervention Actions for Curriculum Change Adoption - Luitel, Sarala; Pokherel, Maheswor; Sharma, Lekhnath; Poudel, Madhav Prasad; Sahani, Suresh Kumar (Journal of Ecohumanism, 2024)
Teacher’s mindset effects on curriculum implementation. A competency-based curriculum focuses on developing competencies in learners rather than transferring knowledge from teacher. There is concern why changed competence-based mathematics curriculum is not implementing well in school. This study, thus, explores the teachers’ mindset and their classroom practices for mathematical competencies development in students. This is an action research based on a qualitative study was planned to intervene some tools expecting to bring changes in teachers’ mindset and influence on classroom practice while implementing the curriculum. The major intervention tools were: a learning outcome log, theme-wise result of learning, and a portfolio. Data were collected using the daily logbook for observation and interview data were kept in written notes. Intervention prior and post changes activities was analyzed based on the seven steps of the Concern Adoption Model (CBAM) as a theoretical base. The results of the study showed the changes in teachers’ mindset and classroom teaching and assessment practices after the intervention justifies the application of concern adoption model for the implementation of the new curriculum as desired.